Towards the assessment of residual biodiversity impacts to support mining rehabilitation and offsets decision-making - Maree, RC (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Global concerns related to the loss of biodiversity and the benefits it provides are rapidly increasing. The extractives industry is responding to this threat, demonstrated by members of the International Council on Mining and Metals (ICMM) who acknowledge that miners, as significant land and water stewards, have responsibility to understand their footprint, mitigate impact and maximise opportunities for the conservation and restoration of nature. This study represents a retrospective application of the biodiversity offset principles for an operational site that has been active for approximately 12 years. Therefore, strict adherence to the mitigation hierarchy was not possible. This assessment presents a case study for the merits of a retrospective application of the mitigation hierarchy, whilst also highlighting aspects to proactively influence decision-making for new projects and future extensions to existing mining operations. Within the scope of the assessed BMUs, the study demonstrates that impacts to BV have either been avoided, resulted in a net gain in BV or resulted in a net loss of BV considering existing offset opportunities. In all cases, the rehabilitation gains do not achieve NNL, requiring offset opportunities to reach NNL or NPI.
Keywords: biodiversity value